OTONOMI DAERAH DI SEKTOR PENANGKAPAN IKAN - Pujo Semedi Hargo Yuwono (Populasi, 2002)
This article attempts to discuss the impact of the enactment of Law No. 22 of 1999 on regional decentralization on maritime areas in Indonesia. The Law No. 22 of 1999 is a clear-cut regulation of the division of management of maritime areas between province and regency (district). The province is entrusted with the task of managing twelve miles off the coast, and one –third of which should be under the jurisdiction of the regency. Scrutinizing of such regulation, the writer is of the opinion that such demarcation of maritime areas will only complicate of problems facing the fisheries sector in Indonesia. Traditional/cultural fishermen consider the sea as an open frontier for everybody. Which is why, whenever there is a party that claims ownership of the sea it, will invite vehement protests from fishermen, as according to them, there is already a mechanism in place to regulate fishing activities. For that reason, the writer recommends the regional government to desist from laying claims to the sea, since they will never be able to effectively control it. The government should instead focus its attention on enforcing the rules of fishing equipment as well as creating competitive fish markets, which should attract fishermen to land their catch in such areas.